Pengaruh Struktur Modal, Struktur Kepemilikan, Karakteristik Perusahaan terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel Intervening pada Perusahaan Sub Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia Tahun 2020 – 2022 - Anggun Veby Safitriana; Hwihanus Hwihanus (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to determine the effect of Capital Structure, Ownership Structure, Company Characteristics on Company Value with Company Financial Performance as an Intervening Variable. This study is a Quantitative Descriptive study using a statistical data analysis method based on Smart PLS4, using a Purposive Sampling Sample Selection Technique where researchers chose to focus research on Pharmaceutical Sub-Sector Companies listed on the Indonesia Stock Exchange in 2020 - 2022. Producing 5 hypotheses and one of them shows a positive and significant effect, namely the effect of Capital Structure on Ownership Structure.